Adhesives for inoculation and pelleting of legume seeds - Faria, S. M. de; De-Polli, H.; Franco, A. A. (Pesquisa Agropecuaria Brasileira, 2014)
The possibility of substituting gum arabic by home-made gums in the inoculation of legume seeds with Rhizobium in mixture with peat was studied. Gums prepared with cassava starch (Manihot esculenta), wheat flour (Triticum aestivum) and araruta starch (Maranta arundinaceae) showed adhesion and stability equivalent to gum arabic. Good pellets were formed using anyone of the gums studied with minercal (calcium hydroxide) fritted trace elements (FTE) or Cofermol (commercial fertilizer containing Co, Fe and Mo). The survival of Rhizobium on the seeds was higher with gum arabic, followed by araruta, cassava and wheat gums. However in all cases, inoculated seeds stored for seven days at room temperature and protected from direct sun light contained more than 104bacteria per seed. The use of water and oil gave poorer results. The nodulation and nitrogen fixation of bean (phaseolus vulgaris) using any of the gums tested was superior to inoculation with water or diesel oil. Nodule efficiency and total nitrogen fixed was increased by pelleting the seeds with FTE-BR9 or Cofermol, probably due to the Mo contained in both fertilizers.